Identical anomalous Raman relaxation exponent in a family of single ion magnets: towards reliable Raman relaxation determination?. Issue 34 (19th August 2020) - Handzlik, Gabriela; Magott, Michał; Arczyński, Mirosław; Sheveleva, Alena M.; Tuna, Floriana; Baran, Stanisław; Pinkowicz, Dawid
Abstract : The results described herein suggest that the exponent n for the temperature dependence of the Raman relaxation process in the series of solid-state diluted isostructural Ln III SIMs should be identical. Abstract : Propeller-like lanthanide complexes with suitable chiral ligand scaffolds are highly desired as they combine chirality with possible magnetic bistability. However, the library of relevant chiral lanthanide-based molecules is quite limited. Herein we present the preparation, structures, magnetic behavior as well as EPR studies of a series of propeller-shaped lanthanide Single Ion Magnets (SIMs). Coordination of the smallest helicene-type molecule 1, 10-phenanthroline- N, N ′-dioxide (phendo) to Ln III ions results in the formation of homoleptic complexes [Ln III (phendo)4 ](NO3 )3 · x MeOH (Ln = Gd, Er, Yb) Gd, Er and Yb, where four phendos encircle the metal center equatorially in a four-bladed propeller fashion. The magnetization dynamics in these systems is studied by magnetic measurements and EPR spectroscopy for non-diluted as well as solid state dilutions of Er and Yb in a diamagnetic [Y III (phendo)4 ](NO3 )3 · x MeOH (Y ) matrix. Careful analysis of the slow magnetic relaxation in the diluted samples can be described by a combination of Raman and Orbach relaxation mechanisms. The most important finding concerns the identical power law τ ≈ T −3 describing the anomalous Raman relaxation for all three reported compounds diluted in the Y matrix. This identical power law strongly suggests that the exponent of the Raman relaxation process in the series of solid-state diluted isostructural compounds is practically independent of the metal ion (as long as the molar mass changes are negligible) and highlights a possible experimental strategy towards reliable Raman relaxation determination.